Teaching Methods Used in the Process of Learning Robotics in General Secondary Schools - Abduganiyev Bekzod Burkhon ugli (Zien Journals, 2022)
this article provides information about the methods of teaching robotics in general secondary schools. Also, the methods that have shown great efficiency in the use of robotics training are mentioned.
Keywords: educational-cognitive; teaching methods; method; passive method